ANALISIS PERAN PEMIMPIN INFORMAL DALAM PELAKSANAAN PEMBERDAYAAN WANITA NELAYAN (STUDI KASUS TENTANG KEGIATAN SOSIAL WANITA NELAYAN DI KEJAWAN LOR KELURAHAN KENJERAN SURABAYA) - Istiqomah Dian Supriati (Faculty of Social and Political Science, 2018)
This research was conducted qualitatively with triangulation approach with snowball sampling method. A total of 8 resource persons were taken in research consisting of formal, informal leaders, fishermen and fishermen mothers. The research took the lo-kasi in the fishing village, namely Kejawan Lor Surabaya. There are eight indicators of leadership to assess the role of informal leaders in empowering mothers of fishermen. Assessment of empowerment is done in two activities that is training activity and activity of Posyandu. The results showed that informal leadership factors such as the ability to give suggestions, support the achievement of goals, catalysts, Representation of empowerment success, source of inspiration and appreciation of the leader proved to be an effective role in leading the empowerment in Kejawan Lor. While the factors of fairness still show weaknesses that need to be improved. The conclusions of this study indicate that in-formal leaders have an effective role to empower citizens.